TRANSFORMATIVE TEACHER LEADERSHIP FRAMEWORK (TTLF): KERANGKA KONSEPTUAL TRANSFORMASI PEMBELAJARAN SAINS - Qoriah Rahmawati; Syadeli (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The demands of twenty-first-century education require learning environments that foster critical thinking, reflection, and meaningful knowledge construction. Although Teacher Leadership Theory, Conceptual Change Theory, and Transformative Learning Theory have contributed significantly to educational research, these perspectives are often examined separately. This study aims to develop the Transformative Teacher Leadership Framework (TTLF) by integrating these theories within science education. An Integrative Literature Review (ILR) was conducted using thematic synthesis consisting of open coding, axial coding, and selective coding. The analysis identified four major themes: transformational teacher leadership as a driver of learning transformation, conceptual change as a mechanism of cognitive transformation, perspective transformation as an indicator of deep learning, and the integration of pedagogical, cognitive, and perspective transformations. Based on these findings, TTLF was developed as a conceptual framework comprising three interconnected dimensions: Pedagogical Transformation, Cognitive Transformation, and Perspective Transformation. The framework positions transformational teacher leadership as a catalyst for conceptual change and perspective transformation, ultimately promoting reflective, critical, and meaningful learning. TTLF contributes to educational theory and provides a foundation for future empirical studies in science education.